2018
DOI: 10.1007/978-3-319-99229-7_40
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of Artificial Intelligence Safety Engineering for Unmanned Aircraft

Abstract: Unmanned aircraft systems promise to be useful for a multitude of applications such as cargo transport and disaster recovery. The research on increased autonomous decision-making capabilities is therefore rapidly growing and advancing. However, the safe use, certification, and airspace integration for unmanned aircraft in a broad fashion is still unclear. Standards for development and verification of manned aircraft are either only partially applicable or resulting safety and verification efforts are unrealist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This hypothesis is broken if AI is embedded in the software of the drone, for example by allowing a learning phase. Although specific drones do not require certification, the assessment of safety critical properties could be problematic by the introduction of AI and, in particular, of the machine learning algorithms, as discussed in [33].…”
Section: Towards Ubiquitous Approaches For Resilience In Acpsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is broken if AI is embedded in the software of the drone, for example by allowing a learning phase. Although specific drones do not require certification, the assessment of safety critical properties could be problematic by the introduction of AI and, in particular, of the machine learning algorithms, as discussed in [33].…”
Section: Towards Ubiquitous Approaches For Resilience In Acpsmentioning
confidence: 99%
“…However, the AI introduction and, in particular, the (on-line or off-line) learning phase overstretch the fundamental hypothesis on which the traditional certification process is based (i.e., the learning phases overstretch reproducibility of proofs that ensure the same system behavior under the same inputs). This situation is also problematic for the category of specific drones (which do not require certification [31,32]) to assess safety-related requirements [30] as discussed in [33]).…”
Section: Towards Certification Approaches For Acpsmentioning
confidence: 99%
“…As an aside, this is also confirmed by AI in aviation (particularly machine learning) still in its infancy. Even if AI is widespread in subdomains such as logistics and fuel consumption estimation [46,47], AI techniques in flight control are rarely found in real-world application scenarios.…”
Section: State Of the Artmentioning
confidence: 99%
“…Yu et al [53] integrated the underlying physics of aircraft dynamic systems into machine learning models, to reduce training costs, and for accurate prediction of flight trajectories. Wang et al [54] introduced a method that mapped the raw sensory data of unmanned aerial vehicle (UAV) into control signals, which enabled the UAVs to autonomously generate suitable trajectories in virtual large-scale complex environments. Schirmer et al [55] introduced current certification practices in unmanned aviation, supported by autonomous systems and AI, and demonstrated that it is possible to use specific operation assessment as an enabler for hard-to-certify techniques.…”
Section: Ai For Ammentioning
confidence: 99%